Dapatkah Bantuan Luar Negeri Mendorong Pertumbuhan Ekonomi ? - Prawoto, Nano (Unisia, 2012)
Foreign debts made by least and less-developed countries, including Indonesia, have different impacts, either positively or negatively, on the economic growth of the countries. This is caused by various factors, such as economic structure, political economy, economic policy, wrong targets, mismanagement, interests of donor countries, and state intervention. Keywords: foreign debts, impacts, economic growth, least and less-developed countries.